Towards a balanced value business model for personalized medicine: an outlook. (January 2013) - Koelsch, Christof; Przewrocka, Joanna; Keeling, Peter
Novel targeted drugs, mainly in oncology, have commanded substantial price premiums in the recent past. Consequently, the attention of pharmaceutical companies has shifted away from the traditional low-price and high-volume blockbuster business model to drugs that command high, and sometimes extremely high, prices in limited markets defined by targeted patient populations. This model may have already passed its zenith, as the impact of more and more high-priced drugs coming to market substantially increases their combined burden on payors and public health finances. This article introduces a new 'balanced value' business model for personalized medicine, leveraging the emerging opportunities to reduce drug development cost and time for targeted therapies. This model allows pharmaceutical companies to charge prices for targeted therapy below the likely future thresholds for payors' willingness to pay, at the same time preserving attractive margins for the drug developers.